2013
DOI: 10.1039/c3tc31015a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced self-assembly of hydrogen bonded P4VP-perylenebisimide comb polymer

Abstract: Polymeric supramolecular assemblies were formed when an unsymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) was complexed with poly(4-vinylpyridine) (P4VP) via hydrogen-bonding interaction. The selfassembly behavior of this polymeric supramolecule poly(4-vinylpyridine)-perylenebisimide P4VP(PDP-UPBI) 1.0 was studied in solvents of varying polarity like chloroform (CHCl 3 ) and methylcyclohexane (MCH). Variable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The aggregation pattern of UPBI‐PDP in thin film exhibited features of both H (blue shifted 0‐0 absorption band) and J (appearance of new red shifted bands around 560 and 580 nm) type aggregates . However, we have attributed it to H type aggregates based on elaborate solution studies involving variable temperature absorption studies etc, which were reported previously …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The aggregation pattern of UPBI‐PDP in thin film exhibited features of both H (blue shifted 0‐0 absorption band) and J (appearance of new red shifted bands around 560 and 580 nm) type aggregates . However, we have attributed it to H type aggregates based on elaborate solution studies involving variable temperature absorption studies etc, which were reported previously …”
Section: Resultsmentioning
confidence: 70%
“…[37][38][39] However, we have attributed it to H type aggregates based on elaborate solution studies involving variable temperature absorption studies etc, which were reported previously. 40 The absorption spectra of drop cast films of the 100% P4VP complexes of the donor and acceptor as well as that for the mixed D-A complexes are given in the Supporting Information (Supporting Information Fig. S8).…”
Section: Absorption and Emission In Thin Filmsmentioning
confidence: 99%
“…The interaction between the polymers and the solvent molecules basically decides the size of aggregation of the polymer in different media. The aggregation behavior is very important as it decides the surface area as well as surface charge of the polymer ,. By changing the media, the aggregation behavior of the PIL can be fine‐tuned and hence its particular application can also be fine‐tuned.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregation behavior is very important as it decides the surface area as well as surface charge of the polymer. [50,51] By changing the media, the aggregation behavior of the PIL can be finetuned and hence its particular application can also be finetuned. For the present case laser diffraction technique was employed for the determination of the size of aggregation.…”
Section: Aggregation Behaviormentioning
confidence: 99%
“…All the samples were recorded in CDCl 3 at a concentration of 10 mg/mL. The proton NMR spectra of the complexes showed prominent broadening of the peaks with shifting corresponding to UPBIPy protons, which was more pronounced in RC . This might be due to the higher content of UPBIPy in RC (49% composition of M2 units in P3HT‐ r ‐P3COOH) compared to only 28% composition of COOH bearing M2 units in P3HT‐ b ‐P3COOH.…”
Section: Resultsmentioning
confidence: 99%